Econometric Analysis of Poverty and Economic Welfare as Predictors of Criminal Activity in Indonesia - A’yun, Kurnia Qurrotul; Azzah Sumaiyah; Wardani, Nabilla Hannah; Zelika, Shinta Devi Arsy; Arip Ramadan; Alhassan Sesay (Journal of Advances in Information and Industrial Technology, 2026)
Criminal activity is defined as a violation of legal mandates and societal standards that triggers communal instability and economic detriment. To address this challenge, identifying the core determinants of such behavior is essential, which this study achieves through a multiple regression methodology. The empirical results demonstrate that Gross Domestic Product (GDP), poverty demographics, per capita spending, and the Human Development Index (HDI) collectively exert a significant influence on national crime rates. This integrated model accounts for 0,775 of the observed variances, as evidenced by the value. Individually, higher levels of GDP, poverty, and HDI correlate with increased criminality, whereas improved per capita expenditure serves as a restrictive factor. These outcomes underscore the necessity of prioritizing welfare enhancement and poverty alleviation within national crime prevention frameworks.